Awareness in Dementia: Development and Evaluation of a Short Version of the Assessment Scale of Psychosocial Impact of the Diagnosis of Dementia (ASPIDD-s) in Brazil. (July 2019) - Dourado, Marcia C.N.; Laks, Jerson; Mograbi, Daniel C.
Abstract : Awareness of disease is defined as the recognition of changes caused by the deficits related to the disease process. We aimed to examine the psychometric properties of the short versions of the Assessment Scale of Psychosocial Impact of the Diagnosis of Dementia (ASPIDD-s), a multidimensional awareness scale. Using a cross-sectional design, we included 201 people with dementia and their family caregivers. The creation of the short versions was based on items with higher loadings on each factor, the correlations between the short versions and demographic or clinical variables and the relevance of the item to the respondent population. Three short versions were created: version 1 and 3, with 12 items and version 2, with 16 items. The short versions correlated very strongly with the full scale and with the 4 factors of the original scale, maintaining the multidimensional nature of the ASPIDD. Loss of awareness was associated with worse quality of life, decreased functionality and cognitive level, and higher caregiver burden across the short versions. Considering the appropriateness of the items and their clinical relevance, we recommend version 3 for use. With only 12 items, the time required for the completion of the scale is short, while maintaining robust psychometric properties.